A comprehensive study of amino acids based ionic liquids as green lubricants for various contacts. (October 2021) - Zhu, Lili; Dong, Jun; Zeng, Qunfeng; Chao, Mianran; Gong, Kuiliang; Li, Weimin; Wang, Xiaobo
Abstract: In this paper, a group of quaternary ammonium amino acid ionic liquids (QAAA ILs) prepared by coupling the tetrabutylammonium cation with fourteen types of natural amino acids as base lubricant were investigated for steel/steel, steel/copper and steel/aluminum contacts at ambient temperature and elevated temperature. The corrosion resistance and tribological ability of various QAAA ILs was determined. The influences of various anionic structures on kinematic viscosity, corrosivity, thermal stability and tribological properties of the ILs were discussed in detailed. The copper strip corrosion test results showed that the present ILs have been proved to be almost non-corrosive. Tribological behaviors results displayed that the present ILs exhibit extremely eminent friction reduction and antiwear properties. Scanning electron microscopy (SEM) and X-ray photoelectron spectroscopy (XPS) analysis revealed that a protective lubricating film is formed on the surface of contact mainly through a polarity induced physical adsorption when QAAA ILs are selected as neat lubricants, which plays a key role in reducing friction and wear between the moving mechanical interface. Graphical Abstract: ga1 Highlights: A series of natural ILs were synthesized by coupling the tetrabutylammonium cation with fourteen types of natural amino acids. The present ILs as base lubricant are almost non-corrosive. Tribological data showed that the ILs exhibit extremely eminent friction reduction and antiwear properties. A protective lubricating film is formed on the surface of contact mainly through a polarity induced physical adsorption.